Rare melanocortin-3 receptor mutations with in vitro functional consequences are associated with human obesity - Mencarelli, M.; Dubern, B.; Alili, R.; Maestrini, S.; Benajiba, L.; Tagliaferri, M.; Galan, P.; Rinaldi, M.; Simon, C.; Tounian, P.; Hercberg, S.; Liuzzi, A.; et al. (Human molecular genetics, 2011)
In contrast to the melanocortin 4 receptor, the possible role of the melanocortin 3 receptor (MC3R) in regulating body weight is still debated. We have previously reported three mutations in the MC3R gene showing association with human obesity, but these results were not confirmed in a study of severe obese North American adults. In this study, we evaluated the entire coding region of MC3R in 839 severely obese subjects and 967 lean controls of Italian and French origin. In vitro functional analysis of the mutations detected was also performed. The total prevalence of rare MC3R variants was not significantly different in obese subjects when compared with controls (P= 0.18). However, the prevalence of mutations with functional alterations was significantly higher in the obese group (P= 0.022). In conclusions, the results of this large study demonstrate that in the populations studied functionally significant MC3R variants are associated with obesity supporting the current hypothesis that rare variants might have a stronger impact on the individual susceptibility to gain weight. They also underline the importance of detailed in vitro functional studies in order to prove the pathogenic effect of such variants. Further investigations in larger cohorts will be needed in order to define the specific phenotypic characteristics potentially correlated with reduced MC3R signalling.